2020
DOI: 10.3390/su12083340
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Climate between Working Excellence and Organizational Innovation: What Comes First?

Abstract: This research introduces a new concept of organizational climate, seen as a "mediator", namely a factor liable to produce positive effects on both individual performances and on work processes and relations, thereby creating a favorable relationship between work excellence and organizational innovation. Health systems have been called to promote sustainability, as actors who work for the health and well-being of their patients. Starting from these considerations, this work shows the main results of a longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…A resilient organizational culture is conducive to shaping a sense of community among organizational members, which can help organizations survive crises. At the same time, a relaxed organizational climate is more conducive to good organizational performance [105]. On the one hand, we should focus on caring and happiness.…”
Section: Discussion and Practical Implicationsmentioning
confidence: 99%
“…A resilient organizational culture is conducive to shaping a sense of community among organizational members, which can help organizations survive crises. At the same time, a relaxed organizational climate is more conducive to good organizational performance [105]. On the one hand, we should focus on caring and happiness.…”
Section: Discussion and Practical Implicationsmentioning
confidence: 99%
“…This study mainly focused on research that indicated that participation and [60] noted that communication has a significant effect on organizational innovation, and a study by Chun (2006) [132] stated that public officials' participation is the most important factor in the techniques for achieving innovation in government organizations. Several other studies have also found that participation and communication have a positive effect on organizational innovation [16,34,36,[56][57][58][59][62][63][64][65][66][67]108,111,[133][134][135][136].…”
Section: Change Management and Organizational Innovationmentioning
confidence: 88%
“…Then, we introduce the methodology Section 3 and describe the findings and discussion Section 4. Lastly, we summarize the findings, present policy implications, and conclude Section 5 [16].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations